Enhancing nutritional value and quality of cookies through pumpkin peel and seed powder fortification - Md. Asaduzzaman; Mst. Sorifa Akter; Mahbubur Rahman (PLoS ONE, 2025)
Background Recently, the pumpkin by-products such as peels and seeds become more and more interesting for confectionary sector, because of the nutritional and bioactive composition. The study was conducted to develop cookies and noodles using different pumpkin by-products (such as peels and seeds) powders in different concentrations and to evaluate the changes in quality characteristics. The powders were prepared from pumpkin seeds and peels. Methodology In this study, various concentrations of pumpkin peel powder (5%, 10%, and 20%) and seeds powder (5%, 10%, 15%, and 20%) were mixed with commercially available wheat flour to produce cookies and noodles. Furthermore, the nutritional, antioxidant, functional and sensory properties of the developed cookies and noodles were evaluated. Result Pumpkin peels and seeds powder and their respective products enrich significantly in protein, fiber, beta-carotene, antioxidants such as total phenolic content (TPC), 2,2- diphenyl-1-picrylhydrazyl (DPPH scavenging activity), Ferric reducing ability (FRAP Ferric reducing power assay), ash content and hunter color values. However, pumpkin seed powder had higher protein content (33.25%) than other powders but pumpkin peel powder (16.83%±1.74) had better fiber content than seeds powder. The highest amount of fiber content was found in 10% pumpkin peel cookies. The analysis of the composition of pumpkin peels and seeds powder has been done in order to further promote their functionality in bakery products based, especially, on wheat flour. Conclusion The best quality and overall acceptable product were obtained when samples were 10% pumpkin peel powder, 15% pumpkin seed powder, and, 10% pumpkin peel powder noodles.